KLF6 facilitates differentiation of odontoblasts through modulating the expression of P21 in vitro - Zhuo Chen; Wenzhi Wu; Chen Zheng; Yanhua Lan; Huizhi Xie; Zhijian Xie (Nature Publishing Group, 2022)
Abstract Multiple signaling pathways are involved in the regulation of cell proliferation and differentiation in odontogenesis and dental tissue renewal, but the details of these mechanisms remain unknown. Here, we investigated the expression patterns of a transcription factor, Krüppel-like factor 6 (KLF6), during the development of murine tooth germ and its function in odontoblastic differentiation. KLF6 was almost ubiquitously expressed in odontoblasts at various stages, and it was co-expressed with P21 (to varying degrees) in mouse dental germ. To determine the function of Klf6, overexpression and knockdown experiments were performed in a mouse dental papilla cell line (iMDP-3). Klf6 functioned as a promoter of odontoblastic differentiation and inhibited the proliferation and cell cycle progression of iMDP-3 through p21 upregulation. Dual-luciferase reporter assay and chromatin immunoprecipitation showed that Klf6 directly activates p21 transcription. Additionally, the in vivo study showed that KLF6 and P21 were also co-expressed in odontoblasts around the reparative dentin. In conclusion, Klf6 regulates the transcriptional activity of p21, thus promoting the cell proliferation to odontoblastic differentiation transition in vitro. This study provides a theoretical basis for odontoblast differentiation and the formation of reparative dentine regeneration.